2014
DOI: 10.7567/apex.7.034001
|View full text |Cite
|
Sign up to set email alerts
|

Planar electron-tunneling Si/Si0.7Ge0.3triple-barrier resonant tunneling diode formed on undoped strain-relaxed buffer with flat surface

Abstract: We demonstrated a planar electron-tunneling Si/Si0.7Ge0.3 triple-barrier (TB) resonant tunneling diode (RTD) formed via a channel layer on an undoped strain-relaxed quadruple-Si1−xGex-layer (QL) buffer. Compared with a conventional vertical Si/Si0.7Ge0.3 TB RTD formed on a heavily doped QL buffer, the dislocation density is low, the surface is flat, and the resonance current density is much larger. These observations, together with analyses of current–voltage (I–V) curve fitting to the physics-based analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We previously reported that a narrowing in the coresonance broadening width in Si 1−x Ge x /Si DQW RTDs is partially caused from an increase in layer flatness, which will also increase the resonance current owing to a more laterally uniform potential. 12) The RMS value for the type-B RTD was typically 0.27 nm, which is smaller than those (∼1.1 nm) for the type-A RTDs by a factor of ∼4.1. No post-annealing to induce the thermal diffusion of impurities for the type-B RTD may result in a flatter surface leading to a larger J R than those for the type-A RTDs.…”
Section: S I 1−x Gementioning
confidence: 83%
See 1 more Smart Citation
“…We previously reported that a narrowing in the coresonance broadening width in Si 1−x Ge x /Si DQW RTDs is partially caused from an increase in layer flatness, which will also increase the resonance current owing to a more laterally uniform potential. 12) The RMS value for the type-B RTD was typically 0.27 nm, which is smaller than those (∼1.1 nm) for the type-A RTDs by a factor of ∼4.1. No post-annealing to induce the thermal diffusion of impurities for the type-B RTD may result in a flatter surface leading to a larger J R than those for the type-A RTDs.…”
Section: S I 1−x Gementioning
confidence: 83%
“…Si 1−x Ge x /Si RTDs have been designed for both hole tunneling [3][4][5][6][7][8][9][10][11] and electron tunneling. [12][13][14][15][16][17][18] Electron-tunneling Si 1−x Ge x /Si RTDs have been generally fabricated using a type-II band lineup with a tensile-strained Si well sandwiched by strain-relaxed Si 1−x Ge x barriers formed on a strain-relaxed Si 1−x Ge x buffer. To relax the Si 1−x Ge x buffer, misfit dislocations are generally introduced between the buffer and a Si substrate.…”
Section: S I 1−x Gementioning
confidence: 99%